Recycling Marble Waste from Afghan Mining Sites as a Replacement for Cement and Sand - Mohammad Rafi Rafi; Safiullah Omary; Amanullah Faqiri; Elhem Ghorbel (Buildings)
The marble industry in Afghanistan generates significant waste due to a lack of skilled labor and advanced machinery, which is often discarded in landfills. Previous studies suggest that marble waste can be utilized in construction, particularly in cement-based structures. This research investigates using marble waste in concrete as a replacement for cement and sand to address environmental concerns and promote sustainability. A comparative study replaced marble waste with a calcareous filler from Omya SAS. The marble waste, collected from a mining site in Nangarhar, Afghanistan, consisted of 29% particles smaller than 63 μm and 71% sand particles. The waste marble (WM) was added to concrete as a replacement for cement and sand at 3.5%, 4%, and 4.5% by volume. Limestone filler (LF) replaced only cement in the concrete mix. The reference concrete mix aimed for a C25/30 strength. The results showed slight improvements in concrete workability with increasing waste marble content. The optimal WM dosage was 4%, which led to a 9% reduction in compressive strength and a 7% drop in splitting tensile strength. However, this dosage reduced concrete density, improving transfer properties and resulting in cheaper, lighter concrete. The 4% WM dosage corresponds to 7.5% cement and 12% sand replacement.